PENDIDIKAN AKHLAK UNTUK PEREMPUAN (TELAAH QUR’AN SURAT AN-NUR AYAT 31) - Badrus Zaman; Desi Herawati Kusumasari (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2019)
The initial idea of ​​this research was that moral education in Indonesia better known as character education still generalized between men and women. Though there are a number of different things between men and women. Of the many verses of the Koran which discuss moral education for women, the Qur'an verse an-Nur verse 31 has more usefulness than the other verses. hThis studyguses abtype ofmlibrarymresearch. The first step is to formulate exactly what you want to study. Then choose the unit of analysis that will be studied, namely choosing the research object that is the target of the analysis. Then analyze the units of meaning and categories and then look for relationships with one another to find meaning and content. The last activity is to describe the results of the analysis. mThe result of the study can be conclude that: First, bowing down aims to maintain dignity as a woman. Secondly, keeping the genitals meant to guard against adultery. Third, do not reveal jewelry except the usual appearance of it, do not intentionally lure the opposite sex with the clothes or accesories he wears. Fourth, the suggestion to cover the veil cloth is to mean wearing a headscarf in accordance with Islamic law.